Opportunities for revitalising the outdoor spaces of historic town centres in Zemgale - Ziemeļniece, Aija; Ločmele, Agnese (Landscape Architecture and Art, 2022)
The study examines the processes of transformation of urban infrastructure and the ways and tools for revitalising the outdoor public spaces of a historic centre. Changes in the historic centres of Auce, Bauska, and Jelgava and their functional layout were identified. A study of usability levels and outdoor public spaces in the historic centre was carried out, resulting in an assessment of the outdoor public space. Based on the study, spatial proposals were made for the development of the historic centres of the three cities. The transformation processes in the urban environment affect social issues, transport infrastructure, land use, water issues, etc. Transformation is taking place at all levels today, from global economic, political, and social structures to the ways the outdoor public space is planned. With the trends of the early 21st century, historic squares are moving towards the revitalisation of these historic locations through recreation and quiet leisure: concerts, exhibition areas, café terraces, also reviving the character of historic fairs. This spurs possible business development, increases the value of property, encourages the presence of green structures, and the introduction of regulation for protected areas in old towns to discourage possible unauthorised activities by their residents. Negative factors in historic centres include urbanisation, physical deterioration, climate change, marketing, and functional obsolescence. Urban revitalisation is viewed as a multi-sectoral strategy that includes the development and implementation of policies in the fields of urban planning, transport, economy, urban development, and sustainability. Solutions can be developed based on different time frames: short-term, cyclical, seasonal, and long-term. The purpose of revitalising the outdoor public space is to improve the social, functional, economic, ecological, and historical aspects of an area through a variety of revitalisation tools.